2005
DOI: 10.2320/jinstmet.69.989
|View full text |Cite
|
Sign up to set email alerts
|

Computer Experiments on Silicon Nano Indentation

Abstract: Computer experiments on silicon nano indentation were performed. Conical shaped rigid indentor was pushed into silicon single crystal under constant load condition. The motion of silicon atoms was calculated using molecular dynamics method, where Stillinger Weber potential was assumed as interaction between silicon atoms. The dynamic load indentation depth curve was calculated and the universal hardness was evaluated from the maximum indentation depth. The obtained value of hardness was similar to the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…According to the results of the previous computer simulation performed by the authors, the indentation depth reached 2.8 nm and the indentation hardness reached 5.85 GPa when the indentation load was set to be 100 nN. 22) The dynamic friction constant varies with time around the average value because the forces F y and F z fluctuate with time, reflecting the dynamic change of the atomic arrangement around the indentor. The standard deviation of ðtÞ, , is calculated and plotted as a function of vertical load in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of the previous computer simulation performed by the authors, the indentation depth reached 2.8 nm and the indentation hardness reached 5.85 GPa when the indentation load was set to be 100 nN. 22) The dynamic friction constant varies with time around the average value because the forces F y and F z fluctuate with time, reflecting the dynamic change of the atomic arrangement around the indentor. The standard deviation of ðtÞ, , is calculated and plotted as a function of vertical load in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The calculation with Tersoff potential succeeded to produce -Sn structure during indentation, 20) while that with SW potential predicted the direct structural transition from crystalline to amorphous or liquid-like disordered structure. 21,22) From these facts, we concluded that Tersoff potential provides more reliable results than SW potential in the simulation of indentation and scratch experiments. It should be noted, however, that SW potential can describe the properties of silicon with diamond, liquid and amorphous structures better than Tersoff potential.…”
Section: Potential Functions and MD Calculationmentioning
confidence: 96%
“…3 Most authors make use of the Tersoff (1988) interatomic potential, which is known to correctly reproduce the cd-Si → β-Si transition. Exceptions are Kallman et al (1993) and Akabane and Sasajima (2005), who used of the simpler Stillinger and Weber (1985) potential, and Goel et al (2014), who chose the analytical bond order potential energy function proposed by Erhart and Albe (2005).…”
Section: Atomistic and Multiscale Modelingmentioning
confidence: 99%
“…To our knowledge,Zarudi et al (2005),Akabane and Sasajima (2005), andGoel et al (2014) are the only works to use a pointed indenter. This is not very surprising, if one considers that on the length scale of MD simulations all real indenters are spherical.…”
mentioning
confidence: 98%